1997
DOI: 10.1136/jmg.34.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Mild myotonic dystrophy is associated with memory impairment in the context of normal general intelligence.

Abstract: Previous investigations of cognitive function in myotonic dystrophy (DM) suggested that DM subjects have impairment of general intelligence and severe defects in executive function. These studies had to neglect patients with mild clinical disease, since they were generally performed before the availability of DNA testing for DM. We have investigated a group of milder DM cases (defined both by their degree of disability and CTG expansion size) and have not found any defect in general intelligence using the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
2
27
1
3
Order By: Relevance
“…Rubinsztein et. al has shown that memory was influenced in early stages of the disease course, rather than executive functions 23 , however, in our study, tests of verbal and memory functions were not found different in control group contrarily.…”
Section: Resultscontrasting
confidence: 90%
“…Rubinsztein et. al has shown that memory was influenced in early stages of the disease course, rather than executive functions 23 , however, in our study, tests of verbal and memory functions were not found different in control group contrarily.…”
Section: Resultscontrasting
confidence: 90%
“…Several authors tried to correlate neuropsychological and neuroimaging findings. 6,24,27,28,45,62,101 Meola et al 71,72 confirmed a selective impairment on tests of frontal lobe function in DM1 and suggested that this type of deficit does not correlate with cortical atrophy and white matter hyperintense lesions, but might be associated with fronto-temporal lobe hypoperfusion on PET studies.…”
Section: Global Intelligencementioning
confidence: 83%
“…Whether measurements of global intelligence correlate with CTG size is a controversial issue. Some authors have concluded that CTG size correlates with IQ or MMSE scores and thus may be of predictive value, 23,47,65,88,101,122 but others have not found any correlation. 71,72,78 Visual-Spatial Deficits.…”
Section: Global Intelligencementioning
confidence: 94%
“…Alterations of personality associated with DM1 include avoidant personality, obsessive-compulsive, passive-aggressive, and schizotypic traits, whose occurrence is not attributable to the patients' disabling condition (Delaporte 1998;Winblad et al, 2005). Other studies have found severe impairment in all measurements of general intelligence and verbal fluency (Rubinsztein et al, 1997).…”
Section: Multisystemic Symptomatologymentioning
confidence: 99%